Experimental investigation of IN725 under different cooling environments using new tool holder. Issue 6 (26th April 2019) - Gupta, Sahil; Venkatesan, K.; Devendiran, S.; Mathew, Arun Tom
ABSTRACT: Heat buildup is an important issue on the cutting edge which then promotes high-temperature wear which consequently leads to poor machinability during dry machining. To improve the machinability, new tool holder designs accommodating cooling techniques have paid considerable attention toward the manufacturing domain recently. Whereas, in this paper, a new tool holder is designed and fabricated to serve for multipurpose cooling arrangements (internal cooling, external cooling) to reduce the heat buildup of the cutting edge along with the consolidated air system to clear away the chips. Initially, need of new tool holder is discussed followed by its manufacturability and machinability characteristics to a machine for nickel alloy Inconel 725. Machinability studies then are compared for dry machining, internal and external wet machining, and tool wear results are discussed. Thus, improvement in tool wear of around 70–75% and 65–72% is observed for internal wet, external wet concerning dry machining, respectively. Whereas, 15–18% (flank wear) and 6–9% (nose wear) improvement are seen for internal wet machining when compared with external wet machining. Results are best understood for internal cooling using a new tool holder.